2019
DOI: 10.1111/are.13999
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use of precipitating agents and ceramic membranes for treatment of effluents with high concentrations of nitrogen and phosphorus from recirculating aquaculture systems

Abstract: Following the culturing of post‐juvenile African catfish, wastewaters were purified using single and integrated processes. Iron coagulant (IC), aluminium coagulant (AC), lanthanum modified bentonite (LMB) and ceramic membranes (NF – nanofiltration) were each tested in single processes, while the combination of IC + NF and AC + NF were used in the integrated process tests. Among the single processes, membrane filtration was the most effective in purifying the aquaculture effluent. The total suspended solids (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…More details regarding the experimental set-up can be found in [ 60 ]. After each filtration, the membrane was chemically cleaned according to the manufacturer’s recommendations, described by Nędzarek et al [ 30 ] and Bonisławska et al [ 61 ]: washing with 2% NaOH solution (T = 360 K, t = 40 min), rinsing with ultra-pure water, washing with 0.5% HNO 3 solution (T = 320 K, t = 30 min), and, finally, rinsing three times with ultra-pure water. Chemical washing resulted in a performance characteristic for a clean membrane.…”
Section: Methodsmentioning
confidence: 99%
“…More details regarding the experimental set-up can be found in [ 60 ]. After each filtration, the membrane was chemically cleaned according to the manufacturer’s recommendations, described by Nędzarek et al [ 30 ] and Bonisławska et al [ 61 ]: washing with 2% NaOH solution (T = 360 K, t = 40 min), rinsing with ultra-pure water, washing with 0.5% HNO 3 solution (T = 320 K, t = 30 min), and, finally, rinsing three times with ultra-pure water. Chemical washing resulted in a performance characteristic for a clean membrane.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, microalgae can be grown without competing for arable land, and in harsh conditions (e.g., salt water) and recirculating systems as an additional component of the water purification system. Such purification systems (photobioreactors producing microalgae biomass) can be successfully used, for example, during intensive fish farming in recirculating aquaculture systems (RAS) where the water is abundant in nutrients necessary for microalgae [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Promising alternatives are processes based on the use of membranes, such as in microfiltration (MF) and ultrafiltration (UF), widely used in the separation, recovery and fractionation of biomolecules from various types of streams, such as wastewaters, byproducts and natural sources [3,6,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ebeling et al (2003) explored the performance of alum coagulation and flocculation to remove total suspended solid parameters from aquaculture wastewater and showed that it had a removal efficiency of up to 92%. Bonisławska et al (2019) highlighted the efficiency of suspended solid removal of up to 100% using the filtration method. Chen et al (2015) indicated the performance of organic matter removal from aquaculture wastewater using ozonation‐membrane filtration with a removal efficiency of 52.1%.…”
Section: Introductionmentioning
confidence: 99%